Design of posicast pida controller using kitti's method - Pannil, Pittaya; Sungsorn, Teenapong; Trisuwannawat, Thanit; Tirasesth, Kitti; Ukakimaparn, Prapart (My University, 2020)
This paper proposes a successful technique for designing a PIDA (proportional-integral-derivative-acceleration) controller in both continuous-time and discrete-time frameworks, which provides better transient response specifications in comparison with PID (proportional-integral-derivative) controller for third-order plant. The proposed design technique consists of three major steps. First, the PIDA controller is designed by using Kitti's method based on root locus technique in the control loop. Second, the maximum percentage overshoot can be decreased to satisfy specification by applying the forward controller. Based on these two steps, all desired specifications can be achieved without trial and error method for tuning controller parameters. Lastly, the Posicast controller is simply designed because the controlled system can be approximated as a standard second-order system. The performances of the designed PIDA controller are confirmed through MATLAB simulation results.
Keywords: Continuous-time/Discrete-time PIDA controllers; Kitti's method; Overshoot; Posicast controller; Third-order plant